2003
DOI: 10.1159/000068890
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Onset Atopic Dermatitis in a Patch Test Population

Abstract: Background: Epidemiological studies about atopic dermatitis (AD) almost exclusively relate to childhood disease with little mention of adult-onset disease. In clinical practice, however, patients who have AD and in whom the onset of disease occurs in adult life are sometimes seen. Objective: Because the subjects with a chronic and recalcitrant eczema are frequently patch tested, the aim of this study was to evaluate the prevalence of adult-onset AD in a patch test population and the differences existing betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 30 publications
4
41
0
Order By: Relevance
“…Recently, Seidenari et al [32 ]have observed positive responses to mite patch tests also in subjects with respiratory atopy and nonatopic subjects without AD, but with a frequency and intensity significantly lower compared to AD patients. In the present work, we have detected a rate of positivity in our patients with AD roughly comparable to rates observed in AD patients by other authors and by us in the past, when the same allergen extracts were employed [11, 13, 19, 20, 23, 24, 32], and we have confirmed in agreement with Seidenari et al [32] that the APT is positive also in AWE and NA subjects, with a frequency significantly lower than in AD patients. Moreover, the evaluation of reading scores confirmed a significant difference of intensity in APT responses in AD patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Recently, Seidenari et al [32 ]have observed positive responses to mite patch tests also in subjects with respiratory atopy and nonatopic subjects without AD, but with a frequency and intensity significantly lower compared to AD patients. In the present work, we have detected a rate of positivity in our patients with AD roughly comparable to rates observed in AD patients by other authors and by us in the past, when the same allergen extracts were employed [11, 13, 19, 20, 23, 24, 32], and we have confirmed in agreement with Seidenari et al [32] that the APT is positive also in AWE and NA subjects, with a frequency significantly lower than in AD patients. Moreover, the evaluation of reading scores confirmed a significant difference of intensity in APT responses in AD patients.…”
Section: Discussionsupporting
confidence: 90%
“…No positive APT responses to aeroallergens in patients with respiratory atopy or controls were detected by Darsow et al [3]. On the contrary, rates of positivities ranging from 5 to 40% in AWE [5, 6, 8, 11, 18, 24] and healthy subjects [6, 8, 9,11,12,13,18,19,20,22,23,24] were reported in the past by other authors. Recently, Seidenari et al [32 ]have observed positive responses to mite patch tests also in subjects with respiratory atopy and nonatopic subjects without AD, but with a frequency and intensity significantly lower compared to AD patients.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Other frequently involved areas were represented by eyelid and periocular area (96/253, 37.9%), hands (dorsal surface) (94/253, 37.2%), neck (81/253, 32%), and labial and perioral area (75/253, 29.6%). Particularly, the common involvement of hands in adult AD patients was also supported by the previous investigations [2,11,14] as the case of eyelid/periocular, neck and labial/perilabial lesions predominance [36], appearing as interesting data which may guide future research trying to establish adult ADspecific diagnostic criteria. Indeed, diagnostic criteria usually used (Hanifin and Rajka and UK criteria) are not completely adaptable in adult patients with a consequent reduction of specificity and sensitivity [14,20,22].…”
Section: Discussionsupporting
confidence: 66%